The effect of product quality and product innovation on customer satisfaction at UD Rohaya Tani Brastagi - Adi Iswanto (Enrichment : Journal of Management, 2023)
Consumer satisfaction is a major milestone in the success of a company, therefore, in an effort to fulfill customer satisfaction, companies must be observant in knowing shifting consumer needs and desires which change at any time. The purpose of this study was to determine and analyze the effect of product quality and product innovation on customer satisfaction at UD Rohaya Tani Brastagi. The research method used is exploratory research, where variables are measured using a Likert scale. Methods of data collection is done by interview (interview), with a list of questions (questionnaire) and study documentation. The population in this study were all consumers at UD Rohaya Tani Brastagi, totaling 92 people. Sampling using saturated sampling method or better known as a census. In this study, the population was relatively small, namely 92 people. Processing data using SPSS software version 23, with descriptive analysis and hypothesis testing multiple regression analysis. The results showed that: (1) partially product quality variables affect customer satisfaction at UD Rohaya Tani Brastagi. (2)partially product innovation variables affect customer satisfaction at UD Rohaya Tani Brastagi ; (3) simultaneously there is a positive and significant influence between product quality and work product innovation variables on customer satisfaction at UD Rohaya Tani Brastagi.